Schistosomiasis was not associated with higher HIV-1 plasma or genital set point viral loads among HIV seroconverters from four cohort studies. - Aaron F Bochner; W Evan Secor; Jared M Baeten; Govert J van Dam; Adam A Szpiro; Sammy M Njenga; Paul L A M Corstjens; Romel D Mackelprang; Nelly R Mugo; Julie Overbaugh; Connie Celum; Andrew Mujugira; et al. (Public Library of Science (PLoS), 2019)
Background Many regions of sub-Saharan Africa experience a high prevalence of both schistosomiasis and HIV-1, leading to frequent coinfection. Higher plasma HIV-1 viral loads are associated with faster disease progression and genital HIV-1 loads are a primary determinant of HIV-1 transmission risk. We hypothesized that schistosome infection would be associated with higher HIV-1 viral loads in plasma and genital samples. Methods/principal findings We utilized data from individuals who HIV-1 seroconverted while enrolled in one of four prospective cohort studies. Plasma and genital viral loads collected 4-24 months after the estimated date of HIV-1 acquisition, but prior to antiretroviral therapy initiation, were included. Detection of circulating anodic antigen in archived blood samples, collected prior to HIV-1 seroconversion, identified participants with active schistosomiasis; immunoblots determined the schistosome species causing infection. Our analysis included 370 HIV-1 seroconverters with plasma viral load results, of whom 82 (22%) had schistosomiasis. We did not find a statistically significant association between schistosomiasis and higher HIV-1 set point plasma viral loads (-0.17 log10 copies/ml, 95% CI -0.38 to 0.03); S. mansoni infection was associated with a lower set point (-0.34 log10 copies/ml, 95% CI -0.58 to -0.09). We found no association between schistosomiasis and cervical (+0.07 log10 copies/swab, 95% CI -0.20 to 0.34) or vaginal (+0.11 log10 copies/swab, 95% CI -0.17 to 0.39) set point viral loads; S. haematobium infection was associated with lower cervical viral loads (-0.59 log10 copies/swab, 95% CI -1.11 to -0.06). Conclusions/significance These results do not support the hypotheses that schistosome coinfection increases plasma or genital HIV-1 viral loads.